Effects of Fully Redundant Dispersity Routing on VoIP Quality - Bettermann, Stephan; Rong, Yue (IEEE, 2011)
Quality and reliability problems are characteristic of real-time services on the Internet such as Voice over IP (VoIP). In this paper the availability of diversity in the Internet is investigated to overcome these flaws. Fully redundant dispersity routing exploits diversity by routing complete copies of the data to be communicated along multiple paths. By actively replicating the data along multiple paths, the effect of a failure on one path may be reduced — or even masked completely — by other paths. This paper presents simulations of such a system, drawing on real VoIP traffic data for the loss, latency and jitter characteristics that data may experience while traversing a path. These simulations show that this form of dispersity routing reduces loss and mean loss burst length, has a de-jittering effect through competition among the paths, and that small numbers of paths already yield significant improvements in deliverable VoIP quality — from 84.12% of calls with which users are estimated as being ‘very satisfied’, to 99.86% using fully redundant dispersity routing with just two paths.